Howard Goldblatt, editor, Chinese Literature for the 1980's. The Fourth Congress of Writers & Artists, New York, M. E. Sharpe Inc., 1982, XVIII + 175 pp. - Cornejo Bustamante, Romer (El Colegio de México, 1983)
-